FACILITATING CONDITION DAN LIFESTYLE SEBAGAI PREDIKTOR PENGGUNAAN LAYANAN BUY NOW PAYLATER (BNPL) : TINJAUAN EMPIRIS DENGAN FINANCIAL LITERACY SEBAGAI VARIABEL MODERASI PADA GEN Z - Adelya Yohana; Abdul Hadi Hari; Junaidi Affan (Kajian Ekonomi dan Bisnis, 2025)
This study investigates the influence of Facilitating Conditions, Lifestyle, and financial literacy on the use of Buy Now Paylater (BNPL) services, a growing trend in digital finance. The purpose of this research is to understand the factors that drive consumer adoption of BNPL services and the role of financial literacy in moderating this adoption. Using a quantitative approach with a correlational design, the study surveyed 500 consumers aged 18-40, selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships among the variables. The results indicate that Facilitating Conditions positively influence the use of BNPL, while Lifestyle, particularly symbolic consumption, also drives BNPL adoption. Additionally, financial literacy plays a mediating role, strengthening the relationship between Facilitating Conditions and Lifestyle on BNPL usage. The findings contribute to the theoretical understanding of consumer behavior in digital financial services and offer practical insights for BNPL providers to improve their platforms by integrating financial literacy programs. Keywords: Buy Now Paylater (BNPL), Facilitating Conditions, Lifestyle, financial literacy, consumer behavior, Structural Equation Modeling (SEM), symbolic consumption.